1997
DOI: 10.1364/ol.22.000555
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive readout of a three-dimensional photochromic optical memory with a near-infrared differential phase-contrast microscope

Abstract: A three-dimensional (3D) rewritable optical memory using photochromic material is described for high-density memory. The bits are recorded in a 3D volume of photochromic material. A transformation of the photochromic molecule between two isomers with different absorption spectra can be stimulated by irradiation with appropriate wavelengths. We show that a nondestructive readout of photochromic memory is possible by use of a small difference in the refractive index of the photochromic isomers in the near-IR ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 10 publications
0
38
0
Order By: Relevance
“…Therefore, a polymeric material is preferred due to its advantages in 3-D erasable storage memory [31][32][33] and the photochromism of complex 1 was investigated in PMMA films.…”
Section: Photochromism Of Complex 1 In Pmma Filmmentioning
confidence: 99%
“…Therefore, a polymeric material is preferred due to its advantages in 3-D erasable storage memory [31][32][33] and the photochromism of complex 1 was investigated in PMMA films.…”
Section: Photochromism Of Complex 1 In Pmma Filmmentioning
confidence: 99%
“…[10][11][12][13] Nishikubo et al [14][15][16][17] reported that polymers containing certain norbornadiene (NBD) moieties in the main and side chains showed high photochemical reactivity, and had a high photo-energy storage capability. NBD is converted to quadricyclane (QC) under UV irradiation, and the resulting polymers are expected to be good photo-energy transformation systems.…”
Section: Calixarene Derivatives As Refractive-index-changing Materialsmentioning
confidence: 99%
“…Photoisomerization is a reversible one and is applicable to write-readerase (WRE) recordings and switching devices. [1][2][3][4][5][6][7] Typical compounds used for photoisomerization are azobenzene, spirobenzopyran, and diarylethene derivatives. Photopolymerization, photolocking, and photoelimination are irreversible reactions, and can be used for readonly holographic memories, waveguide lithography, microlenses, and other optical elements.…”
Section: Introductionmentioning
confidence: 99%